Viewboard Implementation Based on Javascript Charts As a Media for Submitting Sales Information on a Green E-Commerce Website Light Cafe - Sunarya, Po Abas; Bernard, Doucette David; Damanik, Dian Maharani (Aptisi Transactions On Technopreneurship (ATT), 2019)
A media that can display information concisely is needed in presenting information effectively and efficiently. Information on the results of the Green Light Cafe sales report can now be easily accessed by top management and staff through the ledger. However, the process of presenting information with ledgers still uses tables, so it is not in line with current technological developments. In this study, 4 (four) methods will be described which are used to overcome 4 (four) problems, as well as 1 (one) solution, namely the implementation of a viewboard with Highcharts charts. The advantage of Green Light Cafe's viewboard is that it can be accessed through the website and mobile, as well as other advantages, namely minimizing the use of paper, so that it can help staff work in registering reports. By applying the graph as a medium for presenting information on the Green Light Cafe viewboard, it causes top management and employees to find out more about sales reports. Thus, it can be concluded that the use of Highcharts graphics is able to improve the quality and overcome the problems found in the Green Light Cafe.